Roleplay: A Tool for Engaging English Language Learners - Vanisree, M.; Bhargav, KVVN Sai; Ontipuli, Divyanshi (Integrated Journal for Research in Arts and Humanities, 2024)
This article examines the advantages of incorporating roleplay into academic environments, with a specific emphasis on its ability to improve communication and promote the acquisition of vocabulary among students. The study explores the design concerns and assessment methodologies used in roleplay exercises in academic settings, emphasising their efficacy in fostering critical thinking, argumentation skills, and a profound comprehension of course material. The study investigates the impact of roleplay activities on learners' readiness for real-life business interactions, acquisition of negotiation skills, and improvement of professional communication in business environments.